(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Advertising, in its deep and profound sense of the term, reminds us all the embroidered drama, inflated emotions, melodious jingles and colorful pictures that form a beautiful collage which form a beautiful relationship between what they share is manifested through the artwork.In today’s time period, advertising plays a vital role in coordinating viewer’s attention. Social advertisements gave the viewer some serious thought about our social issues. The primary purpose of social advertising is to educate the masses through the hard hitting advisory message.Now days, Celebrity endorsement is widely used to promote awareness regarding the social issues faced in our society. Some great personalities did social awareness campaigns in our country and most of them got success also. In this Paper, some important social awareness campaigns have been discussed in which India’s most successful celebrities were involved. They were succeeded not only to aware people about the social issues, but they also encourage other people to participate and stand out to solve the issues. There are lots of other examples of celebrity endorsement which is discussed in this paper who gave their contribution in delivering the effective social awareness messages.This paper uses the lens of culture to show that Celebrity endorsement can add extra charm and impact on the social message. But the celebrity should be used effectively who can easily conveyed people about the social messages in their social ad campaigns.